ANALISIS KEUANGAN PERUSAHAAN DAERAH AIR MINUM (PDAM) DI JAWA TMUR (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2012)
This research was conducted to know financial performance of Jawa Timur Public Utility of Water Drink (PDAM) and the main factor of financial ratio that determined financial performance Jawa Timur PDAM. Research periods were 2009 – 2010. Population of this research was 24 PDAM and only 14 PDAM had meet criterion of sampling. Financial ratio that used in this research were long term debt-asstes ratio, working capital turnover ratio, receivable turnover ratio, cash ratio, net profit margin ratio, operating ratio and return on assets. Discriminant analysis was used to know which financial ratio that make different between profitable PDAM and loss PDAM. The result of this research shown that working capital turnover ratio, receivable turnover ratio, cash ratio, net profit margin ratio and return on assets of profitable PDAM more better than loss PDAM. Beside that long term debt-assets ratio and operating ratio of loss PDAM higher than profitable PDAM. Discriminant analysis shown that net profit margin ratio and operating ratio were discriminated between profitable PDAM and loss PDAM.